The development and validation of a toolkit to measure consumer trust in food. (April 2020) - Benson, Tony; Lavelle, Fiona; Spence, Michelle; Elliott, Christopher T.; Dean, Moira
Abstract: Consumer trust is an important aspect in the functioning of any market but particularly the food and drinks sector. Food safety incidents and changes in food production practices have simultaneously led to a decrease in consumer trust and a need for greater trust. Previous research has developed items to measure consumer trust in food, however, these have not always been subject to validity and reliability testing and there exists no collated toolkit or collection of items to measure trust in various aspects of the food system. Therefore, the current set of studies aimed to develop a valid and reliable consumer trust toolkit which can be used to measure trust in specific aspects of the food system. Study 1 consisted of a literature review of previous consumer trust measures to construct an initial toolkit of items, followed by an exploratory factor analysis ( n = 481) to identify the structure of the toolkit. Study 2 ( n = 1, 027) used confirmatory factor analysis to verify the factor structure of the model from study 1 with six different factors (types of trust): Organisation trust, product trust, interpersonal trust, trust in the food chain, organisation distrust, and general distrust. Study 2 also established the validity of the toolkit (face validity, convergent validity, and discriminant validity). Study 3 resampled a collection of individuals from study 2 ( n = 247) to establish composite reliability and temporal stability (test-retest reliability). The resultant consumer trust toolkit provides a valid and reliable collection of items which can be used in future research to measure consumer trust in selected aspects of the food system. Highlights: A consumer trust toolkit to measure trust across the food chain was developed. Six different types of consumer trust in the food chain can be measured. The trust toolkit was found to be valid and reliable across multiple countries. Researchers can pick and adapt items from the toolkit depending on their aims.